Pengaruh Model Pembelajaran Kooperatif Tipe Jigsaw Terhadap Meningkatkan Hasil Belajar Siswa di SMA Negeri 1 Biluhu - Rahayu R Ahmad; Radia Hafid; Agil Bahsoan; Rosman Ilato; Sudirman Sudirman; Fatmawaty Damiti (State University of Gorontalo, 2023)
This research uses a quantitative approach with an ex-post-facto research method. The primary dara obtained were from the distribution of questionnaires and gained 62 respondents as a sample from students in clss XI of Ips SMA Negeri 1 Biluhu in ecomonics subject. Data analysis techniques utilized simple regression analysis and were accompanied by an SPSS application. The results of this study showed that the jigsaw-type cooperative learning model has a positive influence on improving students “learing outcomes in economics subject in class XI of IPS at SMA Negeri 1 Biluhu. Through jigsaw-tipe cooperative learning model, students” learing ability might influence the learning outcomes, besides, leaering ability in economics class had a considerable influence 0f 88,5%, while the remaining 11,5% was influenced by other variables that were not studied.